Place-To-Place Migration: Some New Evidence - Fields, Gary S. (The Review of Economics and Statistics, 1979)
[Excerpt] This paper presents new evidence on the determinants of place-to-place migration in the United States. For understanding the causes of differential migration rates into and out of labor markets, knowledge of place-to-place migration functions is of interest for a number of reasons. Given a thorough understanding of gross place-to-place flows, one can proceed to calculate net flows; the reverse, of course, is not possible. There are also other advantages of place-to-place studies: parallelism to microeconomic behavior, opportunity to investigate specific 'origin-destination match-ups, recognition of the number and location of alternative opportunities for persons residing in different origins, and exploration of possible asymmetries. Following a large body of economic literature, the analytical approach adopted regards migration as a form of human investment. Economic variables used in the empirical-work exhibit effects in the hypothesized direction and explain up to two-thirds of the variance in intermetropolitan migration rates. However, this high degree of explanatory power is achieved only for certain functional specifications involving particular independent variables. Thus, the empirical results confirm the usefulness of the human investment approach to place-to-place migration, but they show too that the economic factors used as explanatory variables must be carefully specified and measured.